Exploring the Meaning of Employee Loyalty through the Lens of Organizational Behavior: A Phenomenological Study in Digital Start-up Firms - Intan Purnama; Nicholas Renaldo; Harry Patuan Panjaitan; Achmad Tavip Junaedi; Suhardjo Suhardjo; Kristy Veronica (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study explores the lived experiences of employee loyalty within digital start-up firms from the perspective of organizational behavior. In an era where employee retention and engagement are critical, especially in dynamic digital start-up environments, understanding how loyalty is formed and interpreted by individuals becomes vital. Using a qualitative phenomenological approach, in-depth interviews were conducted with employees from various Indonesian digital start-ups to uncover the underlying meanings and personal interpretations of loyalty. The findings reveal that employee loyalty is perceived as a complex, evolving construct influenced by emotional attachment, shared values, autonomy, and mutual commitment. Loyalty was not merely transactional or tenure-based, but rather closely linked to personal growth, identity, and value alignment, especially among Millennial and Gen Z employees. This study contributes to organizational behavior literature by offering a nuanced view of loyalty that transcends traditional models, emphasizing the importance of intrinsic motivation and purpose-driven work in fostering long-term commitment. The results also offer practical implications for digital start-up leaders to cultivate environments that support psychological engagement, employee well-being, and sustainable loyalty.